Сучасний стан та перспективи біотехнологічних методів виробництва амінокислот - Васильківська, М. К.; Пенчук, Юрій Миколайович (My University, 2012)
Розглянуто сучасні біотехнологічні методи виробництва амінокислот, такі як розділення рацематів, метаболітична і генетична інженерія та ферментативний синтез. В роботі розглянуто основні продуценти амінокислот, а також шляхи підвищення їх біосинтетичної здатності. The modern biotechnological methods for production of amino acids, such as the separation of racemates, enzymatic synthesis, metabolic and genetic engineering. This paper describes the main producers of amino acids, as well as ways to increase their biosynthetic abilities. In recent years, for new and effective strains producing amino acids began to apply the newest techniques of biotechnology. Methods of genetic engineering allow to increase the number of genes of the biosynthesis by cloning them in plasmid. This leads to an increase in the number of enzymes responsible for synthesis of amino acids, therefore, increases the yield of the desired product.
Keywords: амінокислоти; amino acids; мікроорганізми; біосинтез; розділення рацематів; microorganisms; biosynthesis; separation of racemates; кафедра біотехнології і мікробіології